Relational Embeddedness and Firm Growth: Comparing Spousal and Sibling Entrepreneurs - Bird, Miriam; Zellweger, Thomas (Organization Science, 2018)
Integrating relational embeddedness arguments with Penrosean growth theory, we compare the growth of firms run by spousal entrepreneurs with firms run by sibling entrepreneurs. We theorize that trust, identification, and mutual obligations—the three facets of relational embeddedness—are more pronounced in spousal teams than in sibling teams, which provides spousal teams with advantages over sibling teams in generating firm growth. Probing a sample of all private firms in Sweden over a three-year period, we find support for this conjecture. Exploring boundary conditions to this baseline relationship, we also find that firm age weakens the growth advantages of spousal teams over sibling teams and that industry experience heterogeneity within the entrepreneurial team reinforces these growth advantages. These results provide important contributions for research on firm growth, the social embeddedness of firms, entrepreneurship, and family business.